2020
DOI: 10.1108/arch-09-2020-0195
|View full text |Cite
|
Sign up to set email alerts
|

Architecture students' satisfaction with and perceptions of online design studios during COVID-19 lockdown: the case of Jordan universities

Abstract: PurposeThe purpose of this study is to examine the attitudes of students in higher educational institutions in Jordan towards the use of online design studios during coronavirus disease 2019 (COVID-19) lockdown and discusses how their use could enhance the learning process.Design/methodology/approach615 undergraduate students studying architecture in Jordanian universities were recruited to explore the factors that constituted and affected their perceptions of online design studios.FindingsThe findings of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 24 publications
4
104
0
Order By: Relevance
“…Concerning the perceived connection with other students and teachers during the lockdown, previous research indicated that students felt less connected with fellow students and teachers than in face-to-face education (Al-Balas et al, 2020;Puljak et al, 2020;Son et al, 2020). Overall, university students indicated that they have missed in-person contact with other students and professors during the lockdown (Puljak et al, 2020) and that communication has been more complicated than in face-to-face education (Alnusairat et al, 2020;Amir et al, 2020;Radu et al, 2020). In Elmer et al (2020) investigation on students enrolled in engineering and natural science programs, students reported fewer study partners and felt significantly more socially isolated.…”
Section: Impact Of Covid-19 On Students' Learning Experiencementioning
confidence: 97%
See 3 more Smart Citations
“…Concerning the perceived connection with other students and teachers during the lockdown, previous research indicated that students felt less connected with fellow students and teachers than in face-to-face education (Al-Balas et al, 2020;Puljak et al, 2020;Son et al, 2020). Overall, university students indicated that they have missed in-person contact with other students and professors during the lockdown (Puljak et al, 2020) and that communication has been more complicated than in face-to-face education (Alnusairat et al, 2020;Amir et al, 2020;Radu et al, 2020). In Elmer et al (2020) investigation on students enrolled in engineering and natural science programs, students reported fewer study partners and felt significantly more socially isolated.…”
Section: Impact Of Covid-19 On Students' Learning Experiencementioning
confidence: 97%
“…On the one hand, previous research reported students' low satisfaction with the support received from their teachers (Alnusairat et al, 2020) and less satisfaction with the classes and assessment methods in distance education compared to classroom learning (Linh & Trang, 2020). This low satisfaction with how teaching was adapted to the online format is associated with an increase in the perceived workload (Alnusairat et al, 2020;Gelles et al, 2020;Son et al, 2020). Furthermore, Khalil et al (2020) pointed out that the issues related to the implementation and quality of online courses can become barriers to the engagement and acquisition of knowledge.…”
Section: Impact Of Covid-19 On Students' Learning Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…The "inevitable" move to the virtual world is most clearly illustrated by Design Studio Teaching. "Architecture students' satisfaction with and perceptions of online design studios during COVID-19 lockdown: the case of Jordan universities" (Alnusairat, et al, 2020) looks at the value which first year students give to hand drawing, model making and presential studio teaching compared to fourth year students.…”
Section: Analytical Reflections On the Emerging Themesmentioning
confidence: 99%